Oxidation behavior of intramolecularly coordinated unsymmetrical diorganotellurides: isolation of novel tetraorganoditelluronic acids, [RR′Te(μ-O)(OH)2]2. Issue 29 (18th June 2019) - Gupta, Anand; Deka, Rajesh; Sarkar, Arup; Singh, Harkesh B.; Butcher, Ray J.
Abstract : The synthesis of a series of tetraorganoditelluronic acids, [RR′Te(μ-O)(OH)2 ]2 has been reported. Abstract : The oxidation reaction of unsymmetrical diorganotellurides, namely, bis[2-(dimethylamino)methylaryl]tellurides [aryl = phenyl (6 ), 2-methylphenyl (7 ), 2, 6-dimethylphenyl (8 ) and 2, 6-diisopropylphenyl (9 )] with meta -chloroperbenzoic acid afforded the first examples of tetraorganoditelluronic acids, [RR′Te(μ-O)(OH)2 ]2, where R = 2-NMe2 CH2 C6 H4, R′ = C6 H5 (10 ), 2-MeC6 H4 (11 ), 2, 6-MeC6 H3 (12 ) and 2, 6- i PrC6 H3 (13 ). The structures of tetraorganoditelluronic acids10–13 were authenticated by single crystal X-ray diffraction studies. From the molecular structures of10–13, it was observed that the sp 3 N-donor atoms, which were initially involved in intramolecular Te⋯N bonding interactions in diorganotellurides6–9, did not interact with the tellurium atoms in tetraorganoditelluronic acids10–13 . The 125 Te chemical shifts for10–13 were considerably downfield shifted as compared with the values observed for the corresponding tellurides6–9 . The relative stabilities of the tetraorganoditelluronic acids10–13 with respect to their lighter analogues (S and Se) have been assessed using DFT calculations.